Free living nematodes in the collection of the Zoological Museum of the Imperial Academy of Sciences in Petrograd - Filipjev, I. N. (Ezheg. zool. Muz., Petrograd, 1916)
Locality: Murman Coast; Cabinet:
Locality: Murman Coast; NeMys doc_id: 3867; English translation by M.M.Haque, Amerind Publ. Co., New Delhi 1973: 1-55 NeMys doc_id: 4788